2014
DOI: 10.1167/iovs.14-14426
|View full text |Cite
|
Sign up to set email alerts
|

Appositional Angle Closure in Chinese With Primary Angle Closure and Primary Angle Closure Glaucoma After Laser Peripheral Iridotomy

Abstract: Approximately two-thirds of PAC and PACG eyes of Chinese patients after LPI had AAC. Plateau iris accounted for less than 50% of AAC. Other factors such as a thick peripheral iris and an anteriorly inserted iris also contributed to AAC. DRPT results suggested AAC might have more functional meaning than plateau iris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A recent study by Yan et al. () demonstrated that appositional angle closure was observed in more than one quadrant of the UBM image in 63.4% subjects. The difference in the ITC prevalence between UBM and swept‐source AS OCT is probably attributable to the fact that swept‐source AS OCT provides 32 B‐scan images per quadrant, whereas UBM gives only one B‐scan image per quadrant with the current protocol (Mishima et al.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent study by Yan et al. () demonstrated that appositional angle closure was observed in more than one quadrant of the UBM image in 63.4% subjects. The difference in the ITC prevalence between UBM and swept‐source AS OCT is probably attributable to the fact that swept‐source AS OCT provides 32 B‐scan images per quadrant, whereas UBM gives only one B‐scan image per quadrant with the current protocol (Mishima et al.…”
Section: Discussionmentioning
confidence: 94%
“…Yao et al (2009) used UBM to assess ACA features qualitatively after LI and reported that appositional angle closure was observed in at least one quadrant in 38.2% of the fellow narrow-angle eyes of acute PAC patients after LI. A recent study by Yan et al (2014) demonstrated that appositional angle closure was observed in more than one quadrant of the UBM image in 63.4% subjects. The difference in the ITC prevalence between UBM and sweptsource AS OCT is probably attributable to the fact that swept-source AS OCT provides 32 B-scan images per quadrant, whereas UBM gives only one B-scan image per quadrant with the current protocol (Mishima et al 2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other mechanisms identified in primary angle-closure eyes include plateau iris syndrome, [14][15][16] thick peripheral iris roll 16,17 and large lens vault (LV). Other mechanisms identified in primary angle-closure eyes include plateau iris syndrome, [14][15][16] thick peripheral iris roll 16,17 and large lens vault (LV).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of anterior segment imaging has objectively enhanced our understanding as to the reason appositional angle closure persists despite a patent peripheral iridotomy. Other mechanisms identified in primary angle-closure eyes include plateau iris syndrome, [14][15][16] thick peripheral iris roll 16,17 and large lens vault (LV). 17 Approximately 20-30% of PACS and PACG eyes continue to have appositional angle closure in the presence of a patent LPI.…”
Section: Introductionmentioning
confidence: 99%